Synthesis, Characterization And Cholinesterase Inhibitory Activity Of Novel Piperidone Grafted Spiro Heterocycles - Yalda, Kia (2014)
Five new series of new spiro-oxindole-pyrrolizine and pyrrolidine hybrids were synthesized employing facile one-pot three-component reaction of linear or cyclic α-amino acids, isatin and various derivatives of N-acryloyl-bis arylidene piperidin-4- ones dipolarophiles. These reactions afforded new mono-spiroheterocycles and bis-spiroheterocycles by changing the ratio of the starting materials from 1:1:1 to 1:2:2 of dipolarophiles, α-amino acid and isatin. These spiro-cycloadducts were further elucidated using elemental analysis, IR, 1-D and 2-D NMR spectroscopy techniques as well as X-Ray crystallographic data. The newly synthesized compounds were also evaluated for their activity against Alzheimer’s disease using Ellman’s colorimetric assay. In this assay the cholinesterase inhibitory activity of the aforementioned compounds were screened in vitro against acetylcholinesterase enzyme (AChE) from electric eel and butyrylcholinesterase enzyme (BChE) from equine serum, which have the major roles in the manifestation and progression of Alzheimer’s disease.